Offshore Carbonate Facies Characterization and Reservoir Quality of Miocene Rocks in the Southern Margin of South China Sea - Janjuhah, H.T. (Blackwell Publishing, 2020)
Carbonate rocks are important hydrocarbon reservoirs around the globe and in Southeast Asia a key one, particularly, is the Central Luconia province. Understanding the internal characteristics, distribution, geometry and lateral extent of these rocks is essential for exploration and production success. Detailed work on Miocene carbonate reservoir facies, north of Bintulu, offshore Sarawak includes qualitative and quantitative analysis of photomicrographs and reservoir quality, considering especially microporosity. Stratigraphically, these carbonates are known as Cycles IV and V and are represented by eight major facies types (F-1 to F-8]. They comprise: coated grain packstone (F-1) (av. Ã = 3, av. Kh = 0.5 mD) (av = Average; Ã = total porosity, and Kh = permeability); massive coral lime grainstone (F-2) (av. Ã = 14.7, av. Kh = 6 mD); oncolite lime grain-dominated packstone (F-3) (av. Ã = 10, av. Kh = 4 mD); skeletal lime/dolo-packstone (F-4) (av. Ã = 15, av. Kh = 4.6 mD); coral (platy) lime mud-dominated packstone (F-5) (av. Ã = 4, av. Kh = 0.5 mD); coral (branching) lime-dominated pack-grainstone (F-6) (av. Ã = 15, av. Kh = 1 mD); cross-bedded skeletal lime packstone (F-7) (av. Ã = 20, av. Kh = 2 mD); and bioturbated carbonate mudstone/chalk (F-8) (av. Ã = 8, av. Kh = 0.8 mD). Study of thin sections reveals that red algae, foraminifera, and corals are the dominant fossil components with a minor admixture of skeletal fragments of echinoderms, bivalves, bryozoans, and green algae. All parameters, e.g., facies characterization, petrography, porosityâpermeability value, and microporosity value were utilized to obtain a reliable reservoir quality. The microporosity value was quantified using digital image analysis software and is significant for recognition of good reservoir quality. Consideration of the presence of microporosity against the total porosity in the carbonate rocks has improved the correlation coefficient (R2) value, which has increased from 0.51 to 0.82. Â© 2020 Geological Society of China